Achievement Of Indonesian Sustainable Development Using Multimoora Analysis - Ni Kadek Eka Jayanthi (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2025)
Sustainable development is a global concept that has become a priority for every country, including Indonesia. As a vast archipelagic nation with diverse regions, Indonesia presents a unique case study in the implementation of sustainable development. One of the key challenges faced by Indonesia is the uneven distribution of development, which tends to be concentrated around major urban centers such as the capital city, while peripheral regions often lag behind. The essence of sustainable development lies in the internalization of environmental, social, and economic impacts in every policy and action taken. It emphasizes the need to ensure that current development efforts do not compromise the ability of future generations to meet their needs. This study employs the MULTIMOORA (Multi-Objective Optimization by Ratio Analysis plus Full Multiplicative Form) analytical technique to evaluate Indonesia’s sustainable development performance. The results demonstrate significant progress in 2022, where Indonesia ranked first across all three MULTIMOORA methods, marking an improvement from third place in 2021. This upward trend indicates the country’s growing commitment to sustainable development principles. The Sustainable Development Goals (SDGs) serve as comprehensive frameworks that provide specific targets and indicators, which are essential in measuring the effectiveness of development initiatives. By aligning national policies with the SDGs, Indonesia can ensure more inclusive, equitable, and environmentally conscious growth. Sustainable development requires that every social and economic activity accounts for its environmental impact to ensure that natural ecosystems can continue to support life—both now and in the future—thus preserving the planet for generations to come.